The Management of Hyperplastic Pulpitis in Immature Permanent Molar Using Vital Pulp Therapy: A Case Report with 12 Months Follow-Up - Anas Mando; Mohannad Laflouf; Yasser Alsayed Tolibah (Case Reports in Dentistry)
Hyperplastic pulpitis is an irreversible type of pulpitis that primarily affects young patients. It occurs when an inflamed pulp becomes exposed due to factors such as dental caries, dental trauma, or other causes. Root canal treatment is commonly employed to manage hyperplastic pulpitis. However, vital pulp therapy can be considered as a less invasive option. The main objective of this treatment is to preserve the vitality and functionality of the remaining pulp tissue. This case report discusses the potential management of hyperplastic pulpitis in an immature molar using vital pulp therapy instead of a full root canal treatment. The report includes clinical and radiographic follow-up at six and twelve months.